A flexible and highly sensitive pressure sensor based on elastic carbon foam. Issue 6 (24th January 2018) - Liu, Weijie; Liu, Nishuang; Yue, Yang; Rao, Jiangyu; Luo, Cheng; Zhang, Hang; Yang, Congxing; Su, Jun; Liu, Zhitian; Gao, Yihua
Abstract : A highly sensitive pressure sensor based on elastic carbon foam with a fraction of cracked carbon microfibers. Abstract : In this paper, we fabricate a flexible elastic carbon foam (ECF)-based pressure sensor by direct carbonization of melamine foams (MF) at 800 °C without using any metal catalyst. The carbonized ECF is composed of a unique 3D interconnected concave triangular carbon network with a fraction of cracked carbon microfibers, and displays abundant micro and meso-porosity. We select the ECF as a sensing material due to its conductive and elastic features, and make a piezoresistive sensor with ultrahigh sensitivity (100.29 kPa −1 ) and reproducible sensing (11 000 cycles) characteristics. Moreover, the pressure sensor is able to distinguish a large pressure range from as low as 3 Pa to 10 kPa. The cheap raw materials, simple fabrication process and satisfactory performance of the pressure sensor make it a promising device for electronic monitoring systems in industrial detection, human motion monitoring and so on.